Cost-effectiveness analysis of seasonal influenza vaccination during pregnancy: A systematic review - Zakieh Ostad-Ahmadi; Sara Boccalini; Amin Daemi; Alireza Mahboub-Ahari (Travel Medicine and Infectious Disease, 2023)
Background: Seasonal influenza vaccination is clinically important and reduces hospitalization costs for pregnant women. However, is it also a cost-effective intervention? Method: We conducted a systematic search of Medline (via PUBMED), EMBASE, SCOPUS, and Web of Science databases. We included any economic evaluation studies that reported Incremental Cost-Effectiveness Ratios for vaccinating pregnant women against influenza. Result: Out of 927 potentially eligible articles, only 14 full texts met our inclusion criteria. In almost all studies, vaccinating pregnant women was a cost-effective and cost-saving strategy. In one study, it was not cost-effective when the researchers used costs and probabilities related to other groups (healthy adults) due to the lack of data for pregnant women. The main factors influencing the cost-effectiveness of the studies were vaccine efficacy and vaccination cost. Conclusion: Influenza vaccination of pregnant women is a cost-effective intervention. More studies on the cost-effectiveness of this intervention in underdeveloped countries are needed. Keywords: pregnancy, cost-effectiveness, cost-utility, cost-benefit, influenza vaccine, women, economic evaluation.